Proposal for the implementation of a safety plan integrating the Deming cycle to minimize scaffolding accidents at height in a multifamily building - Palomino, Anthony Edwards Arroyo (2023)
The article below presents the application of a safety plan based on the Deming cycle, also known as the PDCA (Plan, Do, Check, Act) cycle, the objective of the research is to minimize scaffolding fall from height accidents in the construction industry workplace. This methodology is effective in improving the quality and productivity of various processes through a continuous improvement approach. The application will be carried out through a series of surveys of workers in a construction company.The implementation process begins with a planning phase in which goals and objectives to reduce scaffolding accidents are defined. The next phase is Doing, in which the designed safety plan is put into practice. Safety measures for scaffolding, personnel training, etc. are implemented. In the third phase of verification, the results of the measures adopted are evaluated, analyzing the data collected in the previous phase to check whether the proposed objectives have been achieved. Finally, in the action phase, measures are adopted on the basis of the results and analysis of the verification phase. If the objectives have been achieved, the measures are implemented on an ongoing basis. If not, areas for improvement are identified and a new action plan is developed to address them. The cycle is continuously repeated and lessons learned are applied in each iteration. Consistent and systematic application of the Deming cycle leads to a gradual improvement in scaffolding safety, thereby reducing the number of accidents caused by falls and contributing to a safer working environment.